Analysis of the fatty acid composition of Caulerpa lentillifera using gas chromatography mass spectrometry - Ab. Halim, Noorhazayti; Zamimi, Nurul Najwa; Sayed Kamar, Syarifah Haizan; Muhammad Ali, Suhaila; Darnis, Deny Susanti; Md Mustafa, Md Muziman Syah (2019)
Caulerpa lentillifera or which also known as Sea Grape or Green Caviar is a type of green seaweed from the class of Caurlepacea, order of Caulerpales, family of Caulerpaceae, genus of Caulerpa and species of Lentillifera They are common components of seaweed communities in tropical and subtropical waters. The presence of various phytoconstituents has been from various seaweed species. Yet, the study on phytochemical components and the biological activity of C. lentillifera are not fully understood yet. Hence, this study was done to determine the best extraction solvents for C. lentillifera and to evaluate the phytocomponent (%) in the n- hexane, Dichloromethane (DCM) and methanol extract of C. lentillifera using Gas Chromatography-Mass Spectrometry (GC-MS) analysis. C. lentillifera was collected from the coastal area of Sabah, Malaysia. Then, it was subjected for purification, drying and soxhlet extraction process using n- hexane, DCM and methanol. Only fatty acid compound was analysed using a Perkin Elmer Turbo Mass Spectrophotometer. Based on the result, , it is proved that, methanol is the most efficient solvent as it recorded the highest extraction yield in C. lentillifera Twenty phytocomponents have been identified from all extracts of C. lentillifera by GCMS analysis. This analysis discovered the presence of major constituents like palmitic acid, oleic acid, pentadecanoic acid, behenic acid, myristic acid,etc. Many studies has shown that, most of the identified major compounds were proven to exhibit antibacterial, antifungal, anti-inflammatory, antiviral, etc. Thus, it is apparent that C. lentillifera have the potential to be used as seaweed of phytopharmaceutical importance as it contains numerous bioactive compounds.